Nutrition Knowledge as a Driver of Adherence to the Mediterranean Diet in Italy - Aureli, Vittoria; Rossi, Laura (Frontiers in Nutrition, 2022)
Background An optimal Nutrition knowledge (NK) among the population could result in greater Adherence to the Mediterranean Diet (AMD), a recognized dietary pattern capable of preventing chronic food-related diseases. This study aimed to evaluate the association between NK and AMD in Italy. Methods A national representative sample of 2,869 adults took part in an assessment that was carried out through a self-administrated questionnaire including sections relating to NK and AMD. AMD was evaluated following the PREDIMED PLUS methodology. Descriptive statistics were provided, and ordinal measures of NK score and AMD were calculated based on quartiles of the quantitative scores. A contingency analysis was performed to check associations between variables. Results In Italy, the average NK score was 50 ± 13.3, equivalent to 56.8% of correct answers. The average value of AMD was 6.8, corresponding to 40% of the maximum score with 31.4% of the population demonstrating low AMD, 31.3% in the lower-middle range, 24% in the medium-high range, and only 13.3% reporting a high AMD. A significant association between NK and AMD was found; respondents who reported the lowest AMD corresponded to those with the lowest NK (36.7%; p < 0.05) and similarly, those with the highest level of adherence to MD also achieved the highest NK scores (41.7%; p < 0.05). Conclusion This study showed that AMD in Italy is generally low, and the strong association between NK and AMD demonstrated that there is a clear connection between a healthy dietary pattern and the nutrition literacy of the population. Those with the highest AMD corresponded to the highest NK and, conversely, those with the lowest AMD displayed the lowest NK. The study also highlighted that socioeconomic aspects were strong determinants of both AMD and NK.